MILK QUALITY MONITORING USING CAPACITIVE SENSOR - Nurzaman, Iman
Nutritional needs contained in milk and probiotics that available in fermented milk, in example, Yakult, are increasing. The challenge is that milk is easily spoiled. Decreasing quality of milk is dependent by microbes and its metabolic activity. The existence of microbes and these activities need to be monitored to be able to overcome the decline in the quality of the milk. The use of sensors based on electric milk products has been developed, in front of using capacitors. The measured capacitance is related to the size of the permittivity or dielectric of the milk product that is sampled. The activity of Lactobacillus casei Shirota strains as lactic acid bacteria, convert sugar to lactic acid. The higher the metabolism, the more sugar that turns into lactic acid and the greater the dielectric. But the amount of sugar and nutrients needed by bacteria will run out, the growth stops, then dies. This change in product composition changes the dielectric properties, and changes the measured capacitance. Capacitance measured by interdigital capacitors and parallel plate as comparison. Capacitance measured in Yakult is greater than pure milk, but changes in capacitance in pure milk are more observed.